BS ISO 11999-5. PPE for firefighters. Test methods and requirements for PPE used by firefighters who are at risk of exposure to high levels of heat and/or flame while fighting fires occurring in structures. Part 5. Helmets (9th August 2023) - British Standards Institution,
No abstract available